2010 IEEE International Conference on Management of Innovation &Amp; Technology 2010
DOI: 10.1109/icmit.2010.5492818
|View full text |Cite
|
Sign up to set email alerts
|

Roles of perceived risk and usefulness in information system security adoption

Abstract: Past research has clarified effective IS security and examined the contributors to security technology adoption in organizations. Based on the research as well as the traditional technology acceptance model, this study proposes a conceptual model that employs risk-related factors to predict managerial attitude towards adopting security technologies. Unlike most works that merely consider perceived usefulness of technology from the positive benefits perspective, this study suggests that the downside of risk is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Lu et al (2005) is one of the few studies that examined and found that perceived risk impacted on intention to adopt an Online Anti-Virus through PU and Attitude towards use. More recently, Chang (2010) proposed an extended TAM model that includes risk-related factors for the prediction of managerial attitude towards the adoption of security technologies within an organisation. Based on findings of significant effects of PR in previous technology adoption studies, we propose that computer users perceiving high risk associated with WBSC will have a negative attitude towards cybersecurity in general.…”
Section: Perceived Risk (Pr)mentioning
confidence: 99%
“…Lu et al (2005) is one of the few studies that examined and found that perceived risk impacted on intention to adopt an Online Anti-Virus through PU and Attitude towards use. More recently, Chang (2010) proposed an extended TAM model that includes risk-related factors for the prediction of managerial attitude towards the adoption of security technologies within an organisation. Based on findings of significant effects of PR in previous technology adoption studies, we propose that computer users perceiving high risk associated with WBSC will have a negative attitude towards cybersecurity in general.…”
Section: Perceived Risk (Pr)mentioning
confidence: 99%